Hospital Image and Compensation/ Benefit System on Organizational Attractiveness - Yu-Hua Yan; Chih-Ming Kung (Public Health, 2017)
Background: Attracting outstanding medical professionals contributes to the creation of a med-ical competitive advantage. This study attempts to compare private and non-profit proprietary hospitals in terms of the connection between hospital image and compensation/benefit system on organizational attractiveness. Methods: The questionnaire survey method was adopted in this study, with employees from two hospitals as applicants. The 1,138 valid questionnaires underwent Pearson correlation anal-ysis and multiple regression analysis. Results: The organizational activeness private and non-profit proprietary hospitals possess structural differences. In private hospitals, the male employees and those under the education background of university have a higher degree of satisfaction towards organizational attrac-tiveness (p<0.1); the male employees in non-profit proprietary hospitals under the age of 30 and needing to shift system have a negative impact on organizational attractiveness (p<0.1). For private and non-profit proprietary Hospitals alike, the corporate image and compensation/benefit system positively affect organizational attractiveness (p<0.1). Conclusion: Talents are important assets for organizational planning strategies, goal accom-plishment, and acquisition of a competitive edge. It is only through the creation of a hospital image and the provision of a sound compensation/benefit system can employees create excel-lent medical services and can hospital competitiveness be enhanced.